Influence of Type of Electric Bright Light on the Attraction of the African Giant Water Bug, Lethocerus indicus (Hemiptera: Belostomatidae) - Luke Chinaru Nwosu; Luke Kosimasichukwu Nwosu (Psyche: A Journal of Entomology)
This study investigated the influence of type of electric bright light (produced by fluorescent light tube and incandescent light bulb) on the attraction of the African giant water bug, Lethocerus indicus (Hemiptera: Belostomatidae). Four fluorescent light tubes of 15 watts each, producing white-coloured light and four incandescent light bulbs of 60 watts each, producing yellow-coloured light, but both producing the same amount of light, were varied and used for the experiments. Collections of bugs at experimental house were done at night between the hours of 8.30 pm and 12 mid-night on daily basis for a period of four months per experiment in the years 2008 and 2009. Lethocerus indicus whose presence in any environment has certain implications was the predominant belostomatid bug in the area. Use of incandescent light bulbs in 2009 significantly attracted more Lethocerus indicus 103 (74.6%) than use of fluorescent light tubes 35 (25.41%) in 2008 [𝑃<0.05; 𝑃(𝑍>4.92)=0.0001]. However, bug’s attraction to light source was not found sex dependent [𝑃>0.05; 𝑃 (𝑍>0.18)=0.4286 and 𝑍>0.28=0.3897]. Therefore, this study recommends the use of fluorescent light by households, campgrounds, and other recreational centres that are potentially exposed to the nuisance of the giant water bugs. Otherwise, incandescent light bulbs should be used when it is desired to attract the presence of these aquatic bugs either for food or scientific studies.